Lugar de mulher: uma cartografia da construção discursiva da liberdade nas revistas femininas - Lôbo, Carolina Cerqueira (2015)
This research investigates how the enunciators of women s magazines deal with the discourses that aim to balance work hours and the possibility of giving up work to have a home life. Our goal is to understand the tension between home life and work in the feminine universe, as well as between the established roles: mother, wife and home queen versus the well succeeded professional. Also this research aimed to unveil the communication contracts between enunciator (magazine) and enunciatee (projected woman reader) and how the magazines convene the permanence or abandonment of the labor market. Our thesis is that the movement of quitting paid jobs promotes a displacement in the hegemonic discourse, bringing up the naturalization of the double working hours: paid employment x caring for home and family (care), which brings care out from invisibility, exposing that the labor market is not as receptive to women as it is thought to be. In order to accomplish this analysis, three monthly magazines directed to the feminine public of different publishing houses were chosen: Cláudia, from Abril; Marie Claire, from Globo e TPM, from Trip. The editions comprise the period from January 2012 to December 2014. This research involves the intersection of two knowledge fields: discourse and feminism. As methodological and theoretical basis the discoursive analysis theories by Ernesto Laclau and Zizek were adopted. On feminism, access to the history of the movement was achieved through Christopher Lasch e Michelle Perrot and also feminism theorists as Donna Willshire, Betty Friedan, Nancy Fraser, Susan Faludi e Ynestra King, among others. To discuss work relations, care theorists such as Eileen Boris and Helena Hirata; Foucault provided support to study Biopolitics